Joint Command for Regional Defense III: Implementation of Eastern Indonesia's Defense Policy in The Communication Dimension - R. Dwi Tjahjo Harsono; Agus Heruanto Hadna; Pande Made Kutanegara; Ahmad Maryudi (Publikasi Indonesia, 2023)
Papua, region in eastern Indonesia which has a separatist movement threatening Indonesia's sovereignty. Soldiers of Indonesia National Army (TNI) as a means of national defense seeks to integrate the TNI's strengths through the establishment of a Joint Defense Area Command III (Kogabwilhan-III) defense policy which covers the Maluku and Papua regions. The communication dimension is seen as important in the success of policy implementation, so the purpose of this research is to analyze the communication dimension in the implementation of Kogabwilhan III policy and identify the factors that influence the implementation of Kogabwilhan III from a communication perspective and what the challenges are. This study using a qualitative descriptive method to explore cases in depth from various sources of information at a certain time. The results of the study explain that the implementation of the Kogabwilhan III policy in the communication dimension has three indicators, i.e. transmission, clarity and consistency indicators. Reviewing the challenges and obstacles, innovation is needed in the communication dimension by adding indicators of local wisdom. Moreover, policy implementation of Kogabwilhan III is divided into two forms of communication: internal communication and external communication.